2003
DOI: 10.2174/1566523034578438
|View full text |Cite
|
Sign up to set email alerts
|

Light Directed Gene Transfer by Photochemical Internalisation

Abstract: Numerous gene therapy vectors, both viral and non-viral, are taken into the cell by endocytosis, and for efficient gene delivery the therapeutic genes carried by such vectors have to escape from endocytic vesicles so that the genes can further be translocated to the nucleus. Since endosomal escape is often an inefficient process, release of the transgene from endosomes represents one of the most important barriers for gene transfer by many such vectors. To improve endosomal escape we have developed a new techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…[1][2][3] Recently, we have developed a technology, generally named photochemical internalization (PCI), for the specific light-directed delivery of different macromolecules, including proteins and genes, into the cytosol of target cells. 4,5 The method is based on photochemical principles also used in photodynamic therapy of cancer (PDT)-a localized cancer treatment involving tumorlocalizing photosensitizers followed by focused light activation. 6 In the PCI technology, photosensitizers localizing in endocytic vesicles are used.…”
mentioning
confidence: 99%
“…[1][2][3] Recently, we have developed a technology, generally named photochemical internalization (PCI), for the specific light-directed delivery of different macromolecules, including proteins and genes, into the cytosol of target cells. 4,5 The method is based on photochemical principles also used in photodynamic therapy of cancer (PDT)-a localized cancer treatment involving tumorlocalizing photosensitizers followed by focused light activation. 6 In the PCI technology, photosensitizers localizing in endocytic vesicles are used.…”
mentioning
confidence: 99%
“…In this scenario, PTD-mediated gene delivery is probably through the non-endosomal pathway [21,55e58]. More recent hypotheses include the artifactual uptake of peptides upon even mild cell fixation [59], improved endosomal escape as the result of photochemical reactions initiated by photosensitization of compounds localized in endocytic vesicles, which induces rupture of these vesicles upon light exposure [60], ATP-and temperature-dependent involvement of endocytosis [59,61], which was subsequently identified as macropinocytosis [24,25,62], clathrin-dependent endocytosis [63] and endosomal acidification [64]. Here, experiments conducted with cells that were pre-incubated for 1 h at 4 C [65] or with 10 mM sodium azide and 6 mM 2-deoxy-D-glucose to deplete cellular ATP [59] revealed that the cellular uptake of 6 Â His-PTD-TopoNs/DNA complexes was energy-and temperature-dependent (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated the disruption of endosomal membranes by reactive oxygen species generated by light activated coincubated photosensitizers (PS) such as porphyrin and phthalocyanine derivatives. This smart strategy was used for controlled and targeted release of endosomally enclosed complexes into the cytosol, thus considerably enhancing nucleic acid delivery with polyplexes [149,150] and PEG-shielded, receptor-targeted systems [64,151,152]. In some applications, however, the PSs applied as separate molecules showed significant phototoxicity due to possible interactions of the PSs with the plasma membrane and cytoplasmic organelles after endosomal escape, inducing cell death.…”
Section: Photochemically Enhanced Transfectionmentioning
confidence: 99%